EVALUATION OF THE IMPLEMENTATION OF THE BASIC SCIENCE CURRICULUM COMPONENT OF THE UNIVERSAL BASIC EDUCATION PROGRAMME IN SOUTH-WEST, NIGERIA (2012)
Most people suffer avoidable health hazard because they lack basic knowledge of science. The old Integrated Science curriculum fell short of what is required to give students a solid foundation in science. The new Basic Science programme is designed to address its inadequacies such as attainment of life and coping skills, and is yet to be evaluated. Even, the previous evaluation studies on the old curriculum were based on its content and not the different components. This study, therefore, evaluated the implementation of Basic Science Curriculum component of Universal Basic Education Programme in South-west, Nigeria. The study adopted descriptive survey design using Stake's countenance Antecedent Transaction Outcome model. Participants were ministry officials (33), principals of schools (89), year tutor/heads of department (166), classroom teachers (269) and JSS III students (588). These were selected by stratified random sampling technique from ten local government areas each from the six south-western states. Five research instruments: Science Programme Objectives Rating Scale (r = 0.72); Basic Science Course Material Assessment Questionnaire (r = 0.81); Basic Science Classroom Observation Schedule (r = 0.73); Basic Science Achievement Test (r = 0.69) and Students' Attitude Questionnaire (r = 0.58) were used. Eleven research questions were answered. Data were analysed using descriptive statistics and multiple regression at 0.05 level of significance. The programme objectives were rated as very good ( = 3.76, max 5). Infrastructural facilities ( = 2.33, max 5) and students achievement in basic science ( = 8.76, max 20) were inadequate and course materials for basic science were available ( = 2.66, max 5). Students possessed positive attitude towards basic science ( = 3.04, max 5), most teachers of basic science were not professionally qualified to teach the subject (66.5%) and many teachers prefer to use lecture method (31.4%) to other methods. Composite contribution of antecedent and transaction variables to the variance of students' achievement in basic science was 10.7% and they contributed 24.7% to the variance of students' attitude towards science. The relative contribution showed that staff training (? = -.407) made negative contribution to achievement in basic science, followed by programme objective (? = -.251) and instructional technique (? = -.084), while manpower requirement (? = .217), availability of text (? = .044) and infrastructure (? = .034) made positive contribution to students' achievement in basic science. Also, availability of text (? = .427) made significant positive contribution to attitude towards science, followed by infrastructure (? = .357) and manpower requirement (? = .090), while instructional technique (? = -.321), programme objective (? = -.197) and staff training (? = -.090) made negative contribution to students' attitude towards science. Availability of text, infrastructural requirement and manpower contribute positively to students' learning outcomes in basic science. Basic Science curriculum component of the basic education programme was not well implemented because right personnel were not engaged in its implementation. Hence, greater effort should be invested in ensuring that in-service training is improved upon to experience positive impact on the implementation of the curriculum.